Hierarchical Nanotube Self‐Assembly of DNA Minor Groove‐Binding Ligand DB921 via Alkali Halide Triggering. Issue 1 (14th August 2019) - Mizuta, Ryo; Devos, Juliette M.; Narayanan, Theyencheri; Oliva, Mizar; Gray, Melissa; Webster, Jessica; Ling, Wai‐Li; Round, Adam; Munnur, Deeksha; Mossou, Estelle; Farahat, Abdelbasset; Boykin, David W.; et al.
Abstract : A systematic study into a novel self‐assembling system is presented whereby the small molecule DB921 forms nearly monodisperse nanotubes upon addition of a suitable salt. Small‐angle X‐ray scattering and negative stain transmission electron microscopy are employed as the principal characterization methods to study both the fundamental assembly processes and reaction kinetics. The assembly is found to be hierarchical, culminating with helical winding of intermediate ribbon structures into nanotubes. The driving force for this process is likely the electrostatic interaction between DB921 and salt anions; this aspect can be used to control nanotube assembly and morphology.